Intelligent privacy preservation proctol in wireless MANET for IoT applications using hybrid crow search-harris hawks optimization - Pamarthi, Satyanarayana; Narmadha, R. (Wireless networks, 2022)
Mobile Ad-Hoc Networks (MANETs) are useful and appropriate, especially for complex scenarios, including law, military enforcement as well disaster recovery, and emergency rescue. Among different cryptographic algorithms, there is a chance of data hacking according to random key generation. The major purpose of this work is to plan and implement a new security protocol in MANET that is applicable for IoT platforms. The approach focused on this research is the modified chaotic map for encryption and decryption to deal with MANET and IoT data. The privacy preservation model is designed with a suggested cryptographic algorithm for enhancing the privacy and security of the MANET and IoT. An enhanced chaotic map is developed for processing the key generation that maintains the encryption and decryption process and prevents the loss of data while recovering the data. The adaptive key management strategy under the chaotic map is developed in this paper using a hybrid meta-heuristic algorithm named Crow Harris Hawks Search Optimization (CHHSO). Finally, the security analysis and performance evaluation in comparison is made in terms of “statistical analysis, convergence analysis, and communication overhead” that show the improved performance of the proposed model.